Kekerabatan Bahasa Melayu Riau, Bahasa Minangkabau, dan Bahasa Batak Toba: Kajian Linguistik Historis Komparatif - Yunisha, Rara; Ermanto, Ermanto (Persona: Kajian Bahasa dan Sastra, 2024)
The research aims to achieve three main objectives. Firstly, it aims to determine the percentage of kinship between BMR, BM, and BBT. Secondly, it aims to determine the duration of separation between these three languages. And thirdly, it aims to describe the form of sound correspondence between them. The research methodology involves both qualitative and quantitative analysis. Qualitative analysis is utilized to describe sound correspondence, while quantitative analysis is employed to calculate the percentage of kinship and the duration of separation. Based on the findings of the data analysis, three conclusions can be drawn. Firstly, the percentage of kinship between BMR and BM is 87.5 percent, between BMR and BBT is 36 percent, and between BM and BBT is 35.5 percent. Secondly, the separation between BMR and BM occurred approximately 306 years ago, and the separation between BMR-BM and BBT occurred around 2,370 years ago starting from 2024. Lastly, sound correspondence was found in 120 vocabularies between BMR and BM, in 188 vocabularies between BMR and BBT, and in 156 vocabularies between BM and BBT out of the 500 research data instruments. In conclusion, the research establishes that BMR, BM, and BBT can be classified as a subfamily of Austronesian parent languages.